دور مصرف سوريا المركزي في الرقابة على عمليات القطع الأجنبي وانعكاساتها على حساباته. (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يقف المصرف المركزي على رأس النظام المصرفي سواء من ناحية الإصدار النقدي أم من ناحية العمليات المصرفيَّة وتحقيق الرِّقابة عليها. وترجع الأهمِّيَّة الكبرى للمصرف المركزي إلى أن تطوُّر الأعمال المصرفية الحديثة ونمو التجارة لكل بلد وما يصاحب ذلك من مزايا يرتبطان بوجود احتياطيات نقدية من العملات الأجنبية خاضعة لإشراف مركزي مما يستدعي قيام المصرف المركزي بمراقبة الكتلة النقدية والائتمان المصرفي تنفيذا لسياسات الدولة الاقتصادية بشكل عام والنقدية بشكل خاص . وحيث أن مصرف الإصدار يحتفظ لديه باحتياطي أو تغطية من القطع فمن هنا برزت أهمية القطع الأجنبي والرقابة عليه، والتي هي نوع من الإشراف الحكومي المنظم على عرض القطع الأجنبي والطلب عيه ،والغرض من ذلك تزويد موارد القطع الأجنبي والتأثير في أسعارها وتنظيم تقلباتها وحركتها حسب ظروف سوق القطع الأجنبي وطبقا للسياسة الاقتصادية. ومن الجدير بالذكر أنَّ تابعية المصرف المركزي لوزارة الاقتصادي يجعله مديريَّة عادية ليس لها سلطة القرار ولا المناقشة بل الانتقال من مرحلة المشرف إلى مرحلة المنفِّذ إلى دائرة تتقيد بالتعليمات , إضافة إلى ذلك يفقد النقد دوره كعنصر مستقل في الاقتصاد ليصبح عنصراً من العناصر الاقتصادية التابعة التي تنفذ وترتبط بالدوائر الأخرى صاحبة السلطة واتِّخاذ القرار. ولهذه الغاية نقوم بدراسة دور مصرف سورية المركزي في الرقابة على القطع الأجنبي وتقييمه وإمكانية تطويره. وقد وضعت الباحثة الفرضين التاليين اللذين استخلصتهما من تحليلها لواقع الرقابة على القطع التي يقوم بها المصرف المركزي: الفرض الأوَّل: إنَّ إلغاء نظام الرقابة على القطع القائم حاليَّاً بما في ذلك القانون 6 لعام 2000م, يؤدِّي إلى زيادة موارد القطع الأجنبي. الفرض الثاني: إنَّ إعطاء الاستقلاليَّة التامَّة للمصرف المركزي يؤدِّي إلى تبسيط الإجراءات وجذب الاستثمارات وبالتالي زيادة حصيلة القطع الأجنبي. وتدعيماً لكلٍّ من الفرضين السَّابقين فقد تمَّ معاينة الواقع العملي لمصرف سورية المركزي, إضافة إلى توجيه عدد من الأسئلة للأشخاص المعنيين وتحليلها وتفسير نتائجها بشكل إحصائي وبناء عليه وضعت الباحثة مجموعة من التوصيات والمقترحات لتطوير دور مصرف سورية المركزي في الرقابة على القطع الأجنبي. The central bank becomes the first of the banking system from the note issue side or the banking operation and attainment of the supervision of it (banking). The paramount importance of the central bank is due to the developments of up to date (new) banking business and trade growth forevery country and the advantages which reliability from that interest by existence of the foreign currency reserves dependent to central supervised ,all that request to selective credit and monetary stock control by the central bank execution to the government economic policy generally and monetary policy specially. For that the issuing bank keeps a foreign currency reserves the import of foreign currency and supervision on it was appeared which is a kind of an organizer government control on the supply of foreign currency and the demand for it and the aim of that is to provide the foreign currency resources and effect in its prices and regulation its movement with the circumstance of the foreign currency market and according to economic policy. And its necessarily to know that the dependence of the central bank to the ministery of economy makes it public management doesn’t have the power of solution and discussion. And its transition from the supevisor phase to Executor phase and to the department limits with the instructions, and also the foreign currency lose it’s role as independent element in the Ecomomy to become an element of dependent Ecomomic elements which Executive and dependent with another departments which have the power of making decision. So we must study the role of the central bank of syria in supervision of exchanging transactions and evoluting this role and possibility of development. And the researcher lays down these two assumptions which infers them by analysis the actual fact of the central bank supervision of exchanging transactions: The first assumption: reversal of supervision of exchanging transaction in this time and the statute No 6/2000 causes in creasing of the foreign currency resources. The secound assumption: if we give the freedom to the central bank it simplifies work and draws investment and increases foreign currency resources. So the resercher analyses the actual fact of the central bank of Syria and operate many questions to the persons whose interest with the subject and analyses them and shows the results. And from that the researcher lays down many of proposals to develop the role of central bank of Syria supervision of Exchanging transactions.